THE INFLUENCE OF PRICE AND SERVICE QUALITY ON COBACO COFFE CUSTOMER SATISFACTION - Fitri Komariyah (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2024)
Indonesia, known for its vast coffee production, has seen a steady rise in coffee enthusiasts within its borders. From 2016 to 2021, the demand for coffee has surged alongside the country's growing population. Among the bustling coffee scene in Jakarta, Cobaco Coffee stands as a prominent coffee shop. With over two decades of establishment, Cobaco Coffee faces competition, particularly in the ready-to-drink sector. The key to their success lies in providing the right balance of price and quality service that caters to the needs of their customers, ensuring a seamless business operation. To gather insights, this study employed primary data collection through questionnaires. Surprisingly, the findings revealed that neither price nor service quality had any significant impact on customer satisfaction. This suggests that other factors may play a more crucial role in determining customer contentment. In order to stay ahead of the competition and continue to thrive in the ever-growing coffee market in Indonesia, Cobaco Coffee may need to adapt their strategies and offerings to better meet the evolving needs and preferences of their customers. This could involve expanding their menu, enhancing their customer experience, or implementing new marketing tactics to attract and retain customers.